The graph of the cosine is an ellipse - Smoluk, Antoni (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
Periodic function – this is a proposition of the new definition – has as its domainthe multiplicative group T = z  C : z = 1 of complex numbers with module one. Therefore a graph of the function f : T  R lies on the cylinder T  R, and so the graph of cosinefunction is the ellipse2212x  y .
Didactics of Mathematics, 2014, Nr 11 (15), s. 59-64
Keywords: domain; graph; periodic function; conditional extrema; cylinder